ЕНЕРГОЕФЕКТИВНА ТЕПЛОУТИЛІЗАЦІЙНА СИСТЕМА ДЛЯ ПІДІГРІВАННЯ ТЕПЛОМЕРЕЖНОЇ ВОДИ ТА ДУТТЬОВОГО ПОВІТРЯ КОТЛІВ КОМУНАЛЬНОЇ ТЕПЛОЕНЕРГЕТИКИ - Navrodskaya, R. A.; Fialko, N. M.; Gnedash, G. A.; Sbrodova, G. A. (Institute of Engineering Thermophysics of NAS of Ukraine, 2017)
The application of the heat recovery- system with the combined use of the recycled heat of the municipal boiler plants is substantiated. The thermal characteristics of the system and the levels of increase in the efficiency of the boiler with a rational ratio of the areas of heat exchange surfaces of water- and air-heating equipment of this system for different regions of Ukraine are determined.